Biomarkers of response and resistance to immune checkpoint inhibitors in breast cancer - Michelle Li; François Panet; Vittoria Barberi; Roberto Salgado; Mafalda Oliveira; Sherene Loi (Breast, 2025)
Immune checkpoint inhibitors (ICIs) have recently been approved in subsets of patients with breast cancer (BC). Currently, programmed death ligand 1 (PD-L1) immunohistochemistry is used as a biomarker of response for metastatic triple negative breast cancer (TNBC). Other tumor-agnostic indications in metastatic BC include high tumor mutational burden and mismatch repair deficiency. In early TNBC, the ICI pembrolizumab is routinely added to neoadjuvant chemotherapy, yet no biomarker is currently available to predict response or resistance. Further, while luminal BC is often thought to be immune-depleted, preliminary efficacy data in early-stage disease suggests that the addition of ICIs to neoadjuvant chemotherapy can significantly improve rates of pathological complete response. However, not all patients will benefit from ICI treatment and it also comes with significant treatment toxicities. This review will describe biomarkers of response and resistance to ICIs in BC. These currently include tumor infiltrating lymphocytes, homologous recombination deficiency, CD274 gain or amplification, estrogen receptor and/or progesterone receptor expression, more precise tumoral immune characterization, gene expression analysis, and the T-cell receptor repertoire. Although still investigational, these approaches hold the potential to advance personalized medicine by tailoring the use of ICIs to BC patients who will benefit.